Trends in functional programming : 19th International Symposium, TFP 2018, Gothenburg, Sweden, June 11–13, 2018, Revised selected papers /: 19th International Symposium, TFP 2018, Gothenburg, Sweden, June 11–13, 2018, Revised selected papers. (2019) - Unknown
No abstract available